Influence of Chemical Composition and Domain Morphology of Li2MnO3 on Battery Properties. Issue 3 (10th December 2020) - Hikima, Kazuhiro; Taminato, Sou; Hinuma, Yoyo; Shimizu, Keisuke; Suzuki, Kota; Hirayama, Masaaki; Yasuno, Satoshi; Tamura, Kazuhisa; Kanno, Ryoji
Abstract: The reaction mechanism, which is the changes that happen during electrochemical cycling, in Li2 MnO3 with a layered rock‐salt (O3) structure was examined using model electrodes in a liquid battery. Epitaxial films of Li2 MnO3 (001) with thickness of 30 nm, various Li/Mn atomic ratios, and different morphologies were fabricated by pulsed laser deposition. These electrodes showed charge–discharge capacity ranging from 150 to 300 mAh g −1, with different degradation characteristics depending on the composition and morphology. Films with nominal (Li/Mn atomic ratio=2.07) and Li‐rich (Li/Mn ratio=2.28) underwent irreversible structural transformation to an activated phase, regardless of the grain size, during the first cycling to 4.8 V. The interlayer spacing increased after activation, which may be a result of a transition to a O1 stacking structure. Li layer and transition metal layer octahedra share faces in the O1 structure, hence, Li diffusion would be easier and therefore results in activation considered to the O1 structure. Further degradation was slower in the nominal film, but the reason cannot be clearly ascribed to composition or grain size. Ex situ hard X‐ray photoelectron spectroscopy (HAXPES) results suggest that some O were oxidized but others were not during charge. The Li‐rich film showed large interactions with a solid‐electrolyte interface layer by virtue of the high Li concentration. Abstract : Influential domain : Epitaxial film electrodes with 30 nm‐thick Li x Mn y O3− z (001) layers of various Li concentrations using pulsed laser deposition under different synthesis conditions. The discharge capacities decreased gradually with cycling at the Li‐rich films with small domain. On the other hand, the capacities of the nominal film with large domain increased continuously with cycling, and no significant capacity fading was observed. Therefore, the severe capacity fading is a characteristic of small domain size in the liquid electrolyte battery.